HOWCAN MULTI- CHANNEL RETAILING FURTHER EXPAND THEIR PRODUCT RANGE WHILST SUSTAINING CUSTOMER EXPERIENCE AND SATISFACTION FOR BOOTS.COM? - Cherian, Bijoy; Lin, Yen-Hui; Mohd Ramli, Mohd Nizaruddin Azlan (2008)
The Nottingham MBA team were assigned to explore online product range extension of Boots.com from marketing, supply chain and financial perspectives. Firstly, from the marketing perspective we explored the market attractiveness, profitability, challenges of expanding the product lines in online industry specifically. Initially we identified the existing customer segments and the emerging customer segments, to better understand the target customers for extending the product line. We also considered market-product life cycle for applying the marketing strategies by considering the market, product and brand parameters by benchmarking with key players in the industry and industry trends. This enabled us to identify the areas of growth for extending the product line for Boots.com. Furthermore, future distribution method 'ÃÂ¢Ã¢ÂÂ¬ÃÂ New Fangled Drop ship model was also evaluated to provide efficient delivery for extended product range in the area of supply chain management. After that, key performance indicators (KPI's) for sustaining customer experience and satisfaction across different channels is also suggested. Lastly we analysed the financial implications of extending the product line, by identifying the key future revenue generators for Boots.com. Considering this as the foundation we developed the hypotheses which were to be answered through the study. H1: For online product expansion in e-retailing, strategic market planning process necessitates careful examination of market attractiveness, typically in shaping market attractiveness, factors such as market size, market growth, competition, segmentation, targeting and positioning, margin potential and the company's core competencies. H2: In moving into new markets, the critical success factors include leveraging on brand/reputation and capability. The timing of products and customer segmentation are important for market attractiveness. H3: Good inventory management, cost-effective and efficient delivery and supply for new product protect margin and profitability. H4: In Key Performance Measurement ('KPI') for sustaining customer experience and satisfaction for Boots.com, Channel Alignment, Drop Ship and Efficient Standardised Delivery Methods for all products are used. The hypotheses were answered through a combination of qualitative and quantitative research methods. For analysing Boots.com internally we looked into Boots.com's internal data which was provided to us from all the perspectives of Sales and Marketing, Supply Chain and Financials. For understanding from customer perspective in terms of new products from marketing view point and understanding the customer experience in terms of delivery methods from multi channel retailing and supply chain view point, we conducted various levels of surveys for collecting the data. This cemented our research and analysis of data we collected from the industry reports. The results and finding reinforced our hypotheses in extending the product line from marketing, supply chain and financial perspectives. Finally, our research and analysis enabled us to recommend the key areas of product line extension for Boots.com and the scope of improvement for the future drop ship model. Based on the screening criteria of market attractiveness and business position, we have recommended five products which can be further maximised and taken further. These products are seen to be financially viable based on the projected future cash flow, projected profit margin, and net present value to signify increasing shareholders wealth. For Boots.com, these financial viability must be accompanied by Key Performance Indicators which are intrinsically linked to continuous improvement. To conclude, we also considered Boots.com's future road map for showcasing the future direction by incorporating these recommendations.